STUDENTS' PERCEPTIONS OF USING KAHOOT AS AN EVALUATION TOOL IN ARABIC LANGUAGE LEARNING - Maulana, Moh. Fikri Jauhar (Kitaba, 2024)
Implementation of learning evaluations often only uses traditional media, namely paper and is corrected manually by the teacher. However, as technology develops, we can use it as an update in carrying out learning evaluations, especially in Arabic language learning. so it can be more time and cost efficient. One form of utilizing technology is using the Kahoot application. Kahoot is a technology-based learning evaluation media with an attractive and completely automatic appearance. This research aims to analyze students' perceptions of the Kahoot application as a medium for evaluating Arabic language learning. This research approach is to use descriptive quantitative research and use a questionnaire as a data collection technique. The population in this study were 54 grade 7 students at Madrasah Tsanawiyah Negeri 9 Nganjuk. The research results show that the use of Kahoot as a medium for evaluating Arabic language learning received a positive response from students. This is because Kahoot is easy to use, has an attractive appearance, and is transparent in displaying scores. So, students are increasingly motivated to study in order to achieve the highest grades possible.